Photodegradation of Rhodamine B and Bisphenol A Over Visible-Light Driven Bi7O9I3-and Bi12O17Cl2-Photocatalysts Under White LED Irradiation - Tuba Guaman, Damian Francisco (2022)
Two different bismuth oxyhalides photocatalysts Bi7O9I3 and Bi12O17Cl2 were obtained by oil bath and hydrothermal methods. The micro/nano-structures obtained were characterized by XRD, SEM, DRS and XPS. The XRD patterns are identical to those already reported. SEM revealed the formation of hierarchical micro/nano structures for Bi7O9I3 and nanobelts for Bi12O17Cl2. Band gap values were determined for both catalysts from DRS and XPS data. The photocatalytic degradation of Rhodamine B and Bisphenol A were studied with both bismuth oxyhalides and compared with commercial titanium dioxide (TiO2). As light source was used a white Light-Emiting Diode lamp. As expected, a poor photocatalytic degradation was obtained in presence of TiO2, but significant drops of concentrations in presence of the bismuth oxyhalides was observed. However, the mineralization of both polluntants was higher in presence of Bi12O17Cl2 than with Bi7O9I3. In addition, a great part of Rhodamine B was removed by Bi7O9I3 in the dark, which is attributed to its morphological features. In contrast, Bisphenol A was degraded under visible light irradiation without significant adsorption.